2010
DOI: 10.3109/01443610903461436
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery or vaginal birth: Preference of Turkish pregnant women and influencing factors

Abstract: The aim of this study was to assess the preference of pregnant women for mode of delivery in an uncomplicated pregnancy and reasons of their choice, also to determine if maternal characteristics were predictors of maternal preference. Pregnant women applying to the antenatal clinic for a routine control visit were recruited. After verbal consents, a questionnaire was administered to 1,588 pregnant women. Of the women questioned, 84.1% opted for vaginal delivery whereas only 15.9% opted for an elective caesarea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
30
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 11 publications
14
30
2
7
Order By: Relevance
“…Among the reasons given for their inclination towards SVD in the current study included quick post-delivery recovery, natural and safe, easy and simple. In part, the current study commensurate with previous reports where SVD was viewed as normal, healthy and a natural sign indicating a successful passage from womanhood to motherhood [15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…Among the reasons given for their inclination towards SVD in the current study included quick post-delivery recovery, natural and safe, easy and simple. In part, the current study commensurate with previous reports where SVD was viewed as normal, healthy and a natural sign indicating a successful passage from womanhood to motherhood [15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, 348 women (%87) preferred vaginal delivery. Similar to us; Buyukbayrak et al [8] showed that of the women questioned, 84.1% opted for vaginal delivery whereas only 15.9% opted for an elective caesarean delivery in Turkey at 2010. Optimal cesarean rate is 15% that WHO recommended [2].…”
Section: Discussionsupporting
confidence: 74%
“…Numerous studies that have been conducted in Turkey indicated causes of women's vaginal delivery preference. These causes was; handle the sense of control, a desire for vaginal delivery experience, and a desire for early recovery and early discharged from hospital, a lower complication rates, fear of anesthesia and operation, safety of mother, better relationship to baby, less painful period after giving birth, the thoughts of 'better for the health' and 'birth is a normal event' and immediate breast feeding [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study carried out in Turkey about CS preference and influencing factors by Buyukbayrak et al [47] who revealed that most of women preferred CS due to fear of vaginal delivery and a fifth of them preferred cesarean section due to their worries about their health, also they saw it as safer mode for their babies. In addition, El-Nemer [41] who reported that the causes of requesting cesarean delivery were fear of normal labour and delivery, safety, less physical damage and less risk for mother and the baby.…”
Section: Discussionmentioning
confidence: 99%